2006
DOI: 10.1042/bj20051916
|View full text |Cite
|
Sign up to set email alerts
|

Localization of GRP78 to mitochondria under the unfolded protein response

Abstract: The ubiquitously expressed molecular chaperone GRP78 (78 kDa glucose-regulated protein) generally localizes to the ER (endoplasmic reticulum). GRP78 is specifically induced in cells under the UPR (unfolded protein response), which can be elicited by treatments with calcium ionophore A23187 and sarcoplasmic/endoplasmic reticulum Ca2+-ATPase inhibitor TG (thapsigargin). By using confocal microscopy, we have demonstrated that GRP78 was concentrated in the perinuclear region and co-localized with the ER marker pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
102
1
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(116 citation statements)
references
References 48 publications
(58 reference statements)
8
102
1
5
Order By: Relevance
“…GRP78, the ER member of the HSP70 family, is regulated by heat and/or other stresses (Shiu et al 1977;Sun et al 2006;Quinones et al 2008). In this paper, we verified that thermal stress and starvation can induce the up-regulation of Bmgrp78 expression in silkworms, especially in head tissues.…”
Section: Discussionmentioning
confidence: 99%
“…GRP78, the ER member of the HSP70 family, is regulated by heat and/or other stresses (Shiu et al 1977;Sun et al 2006;Quinones et al 2008). In this paper, we verified that thermal stress and starvation can induce the up-regulation of Bmgrp78 expression in silkworms, especially in head tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using transmembrane prediction programs have suggested that GRP78 has four potential transmembrane domains at the cell surface: I (amino acids (aa) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17], II (aa 29 -45), III (aa 222-242), and IV (aa 414 -431) (34). However, the studies performed here demonstrate that at least residues 416 -417 are exposed on the cell surface, as this is the sole SubA cleavage site, and we observe cell-surface cleavage.…”
Section: Discussionmentioning
confidence: 99%
“…Normal cellular function is, therefore, reestablished by reducing intermediate protein aggregates, increasing protein folding, regulating Ca 2ϩ , and repressing translation (1). In addition to its role as a molecular chaperone in the ER, GRP78 is found in the cytoplasm, nucleus, and mitochondria, and it exists in secreted and plasma membrane-associated forms (2)(3)(4)(5)(6). At the plasma membrane, GRP78 acts as a signaling receptor for activated ␣ 2 -macroglobulin (␣ 2 M*) (7,8).…”
mentioning
confidence: 99%
“…GRP75 directly interacts with both VDAC and IP3R, playing a central role in scaffolding this ER-mitochondrial complex [87]. Translocation of GRP78 from ER to mitochondria observed following ER stress [88] or ischemia-like stress [86] may also play a key role in the ER-mitochondria crosstalk during cerebral ischemia [86]. Chaperone complexes at both the ER and mitochondrion orchestrate the regulation of Ca 2+ signaling between these two organelles and control bioenergetics, cell survival, and cell death decisions.…”
Section: Mirnas and Chaperonesmentioning
confidence: 99%